Fraktur tibia terbuka tipe III C - Armis Armis (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Seven patients of open tibial fractures type III C were treated in the Emergency Unit, Sardjito hospital from 1990 to 1995. Three patients underwent early amputation and four patients ultimately required secondary amputation from three to twelve days after vascular repair intervention.Open tibial fractures associated with vascular trauma need an immediate decision between early amputation and limb salvage. Prospective studies are important before a well-defined protocol or objective criteria for early amputation can be considered.Key word : open fracture – tibial fracture – lower fracture – type Ill C – amputation